2009
DOI: 10.1016/j.jneuroim.2009.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Immunodominant epitope and properties of pyroglutamate-modified Aβ-specific antibodies produced in rabbits

Abstract: N-truncated and N-modified forms of amyloid beta (Aß) peptide are found in diffused and dense core plaques in Alzheimer's disease (AD) and Down's syndrome patients as well as transgenic mouse models of AD. Although the pathological significance of these shortened forms Aβ is not completely understood, previous studies have demonstrated that these peptides are significantly more resistant to degradation, aggregate more rapidly in vitro and exhibit similar or, in some cases, increased toxicity in hippocampal neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…This region also includes the strongly immunogenic N-terminal sequence of soluble Aβ. 32 Since we wanted an inhibitor that selectively binds APP but not Aβ, we first performed a negative selection using FACS to remove clones that bound Aβ. While some strong Aβ binders did remain, as evidenced by the recognition of Aβ by the strongest binders in the P1 pool (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This region also includes the strongly immunogenic N-terminal sequence of soluble Aβ. 32 Since we wanted an inhibitor that selectively binds APP but not Aβ, we first performed a negative selection using FACS to remove clones that bound Aβ. While some strong Aβ binders did remain, as evidenced by the recognition of Aβ by the strongest binders in the P1 pool (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gevorkian and coworkers [37,38] reported the use of pyroglutamate-modified A as a new antigen in A immunotherapy. Zvirbliene and coworkers [39] showed the size of A oligomers may influence the immune response.…”
Section: New Antigenic Peptidesmentioning
confidence: 99%
“…In addition, AβN3(pE) was shown to induce a redox-sensitive neuronal apoptosis involving caspase activation and an arachidonic acid-dependent pro-inflammatory pathway in primary neuronal cultures [41]. Recently, our group demonstrated that AβN3(pE) oligomers induce phosphatidylserine externalization and membrane damage in differentiated SH-SY5Y cells [56]. Moreover, AβN3(pE) was shown to inhibit long term potentiation in mouse hippocampal slices [54].…”
Section: Pyroglutamate-modified Aβ Peptidesmentioning
confidence: 99%
“…In recent years, a couple of laboratories started to include pyroglutamate-modified Aβ in their research agenda. Our group performed first studies on immunogenicity of AβN3(pE) and AβN11(pE) in rabbits and demonstrated that while AβN3(pE) peptide induces antibodies specifically binding to AβN3(pE), anti-AβN11(pE) antibodies recognize two pyroglutamate species, AβN3(pE) and AβN11(pE), and full-length Aβ as well [56, 88]. The latter results suggest that AβN3(pE), AβN11(pE) and full-length Aβ may share a common B cell epitope, and are important for designing immunogens capable of inducing antibodies targeting three main pathological species of the Aβ peptide present in human brain.…”
Section: Possible Treatment Strategiesmentioning
confidence: 99%
See 1 more Smart Citation